Penerapan Creative And Design Thinking Sebagai Strategi Pengembangan UMKM Di Kota Cirebon - Denni Pratama; Kaslani; Indra Wiguna Marthanu; Mochammad Rifqi Aqila (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Cirebon City hold considerable potential in the culinary, fashion, handicraft, and service sectors, yet many business owners still struggle to generate original business ideas, formulate customer-centered solutions, and survive the early, failure-prone stages of running a business. This community service activity aims to strengthen the capacity of MSME actors in Cirebon City to apply creative thinking and design thinking as a user-centered approach to business problem-solving. The implementation method uses a participatory training approach consisting of needs identification, interactive lectures and discussion, and simulation of the design thinking stages, namely empathize, define, ideate, prototype, and test. Participants were also introduced to the characteristics of creative thinking, namely fluency, flexibility, originality, and elaboration, as well as the common causes of small business failure. The results show an improvement in participants' understanding of the distinction between creative and critical thinking, their ability to identify business opportunities, and their ability to formulate customer-centered solution ideas through the design thinking stages. This activity confirms that strengthening creative and user-centered thinking capacity needs to be integrated continuously into MSME mentoring in Cirebon City to enhance innovation, efficiency, and business competitiveness.